Biological and Ecological Characteristics of Red Bayberry (Myrica rubra) in Cao Ma Po Commune, Quan Ba District, Ha Giang Province - Khang, Nguyen Sinh; Hien, Nguyen Thi; Thai, Tran Huy; Ha, Chu Thi Thu; Hanh, Nguyen Phuong; Thinh, Nguyen Duc; Hieu, Nguyen Quang; Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 3, 2018)
Red bayberry ( Myrica rubra (Lour.) Siebold & Zucc.) natively grows in evergreen broad-leaved forests at the elevation of 1580-1875 m a.s.l. and can survive in low nutrient soil in Cao Ma Po commune, Quan Ba district, Ha Giang province. Data on morphology, phenology, population structure, natural regeneration and distribution of Red bayberry; climatic characteristics, physical and chemical properties of soil, and vegetation structure of forests with Myrica rubra are presented in this paper. Keywords Red bayberry, biology, ecology, conservation, Ha Giang, Vietnam References [1] Lu A. & Bornstein A. J., Myricaceae in Wu Z. Y. & Raven P. H. (eds.). Flora of China Vol. 4, Science Press & Missouri Botanical Garden Press, Beijing & St. Louis, 1999, pp. 275-276. [2] He X. H., Chen L. G., Asghar S. & Chen Y., Red Bayberry (Myrica rubra), a Promising Fruit and Forest Tree in China, Journal of the American Pomological Society, 58(3), 2004, pp. 163- 168. [3] Joyce D., Khurshid T., Liu S., McGregor G., Li J. & Jiang Y., Red Bayberry-A New and Exciting Crop for Australia? An investigation of the potential for commercialisation of Myrica rubra Sieb. and Zucc. (Yang mei) in Australia, RIRDC Publication No. 05/081, 2005, 26 pp. [4] Sharpe R. H. & Knapp F. W., The Straberry tree, Myrica rubra Sieb. and Zucc., Florida State Horticultural Society, 1972, pp. 326-328. [5] Chai C. Y. & Chen Y. F., Introduction of Yangmei Elite Varieties in California, World Journal of Forestry, 5(1), 2016, pp. 1-6. [6] Fang Z. X., Zhang M., Tao G. J., Sun Y. F. & Sun J. C., Chemical composition of clarified bayberry (Myrica rubra Sieb et Zucc.) juice sediment, Journal of Agriculture and Food Chemistry, 54(20), 2006, pp. 7710-7716. [7] Cheng J. Y., Ye X. Q., Chen J. C., Liu D. H. & Zhou S. H., Nutritional composition of underutilized bayberry (Myrica rubra Sieb. et Zucc.) kernels, Food Chemistry, 107(4), 2008, pp. 1674-1680. [8] Joyce D. & Sanewski G., The Commercial Potential of Red Bayberry in Australia, RIRDC Publication No. 10/200, 2010, 36 pp. [9] Zhang X. N., Huang H. Z., Zhao X. Y., Lu Q., Sun C. D., Li X., Chen K. S., Effects of ﬂavonoids-rich Chinese bayberry (Myrica rubra Sieb. et Zucc.) pulp extracts on glucose consumption in human HepG2 cells, Journal of Functional Foods, 14, 2015, pp. 144-153. [10] Tong Y., Zhou X. M., Wang S. J., Yang Y. & Cao Y. L., Analgesic activity of myricetin isolated from Myrica rubra Sieb. et Zucc. leaves, Archives of Pharmacal Research, 2(4), 2009, pp. 527-533. [11] Zhang Y., Zhou X. Z., Tao W. Y., Li L. Q., Wei C. Y., Duan J., Chen S. G. & Ye X. Q., Antioxidant and antiproliferative activities of proanthocyanidins from Chinese bayberry (Myrica rubra Sieb. et Zucc.) leaves, Journal of Functional Foods, 27, 2016, pp. 645-654. [12] Kim H. H., Kim D. H., Kim M. H., Oh M. H., Kim S. R., et al., Flavonoid constituents in the leaves of Myrica rubra Sieb. et Zucc. with anti-inflammatory activity, Archives of Pharmacal Research, 36(12), 2013, pp. 1533-1540. [13] Kuo P. L., Hsu Y. L., Lin T. C., Lin L. T. & Lin C. C., Induction of apoptosis in human breast adenocarcinoma MCF-7 cells by prodelphinidin B-2 3,3'-di-O-gallate from Myrica rubra via Fas-mediated pathway, Journal of Pharmacy and Pharmacology 56(11), 2004, pp. 1399-1406. [14] Sun C. D., Zheng Y. X., Chen Q. J., Tang X. L., Jiang M., Zhang J. K., Li X. & Chen K. S., Puriﬁcation and anti-tumour activity of cyanidin-3-O-glucoside from Chinese bayberry fruit, Food Chemistry, 131(4), 2012, pp. 1287-1294. [15] Sun C. D., Huang H. Z., Xu C. J., Li X. & Chen K. S., Biological activities of extracts from Chinese bayberry (Myrica rubra Sieb. et Zucc.): A review, Plant Foods for Human Nutrition, 68(2), 2013, pp. 97-106. [16] Langhansova L., Hanusova V., Rezek J., Stohanslova B., Ambroz M., et al., Essential oil from Myrica rubra leaves inhibits cancer cell proliferation and induces apoptosis in several human intestinal lines, Industrial Crops Products ,59, 2014, pp. 20-26. [17] Ambrǒz M., Bousǒvá I., Skarka A., Hanusǒvá V., Králová V., et al., The Influence of Sesquiterpenes from Myrica rubra on the Antiproliferative and Pro-Oxidative Effects of Doxorubicin and Its Accumulation in Cancer Cells, Molecules, 20(8), 2015, pp. 15343-15358. [18] Lê Mộng Chân và Lê Thị Huyền, Thực Vật Rừng, Nxb Nông nghiệp, Hà Nội, 2000, tr. 149-150. [19] Xia N. H., Myricaceae in Hu Q. M. & Wu D. L. (eds.), Flora of Hong Kong Vol. 1, Agriculture, Fisheries and Conservation Department, Hong Kong, 2007, pp. 125-126. [20] Nguyễn Sinh Khang, Bùi Hồng Quang, Vũ Tiến Chính, Nguyễn Tiến Hiệp, Nguyễn Quang Hiếu, Nguyễn Thành Sơn, Xia Nian He & Davidson Christopher, Myrica rubra (Lour.) Siebold & Zucc. (Myricaceae): A useful plant resource in Vietnam, Hội nghị Khoa học toàn quốc lần thứ 7 về Sinh thái và Tài nguyên sinh vật, Viện Sinh thái và Tài nguyên sinh vật, Nxb Nông nghiệp, Hà Nội, 2017, pp. 226-232. [21] Nguyễn Nghĩa Thìn, Các phương pháp nghiên cứu thực vật, Nxb. Đại học Quốc gia Hà Nội, Hà Nội, 2007. [22] Liesner R., Field Techniques Used by Missouri Botanical Garden, 2018, http://www.mobot.org/MOBOT/molib/fieldtechbook/welcome.shtml [23] Bộ Khoa học và Công nghệ, Tiêu chuẩn Việt Nam TCVN 7538-2:2005 (ISO 10381 - 2 : 2002) về Chất lượng đất - Lấy mẫu - Phần 2: Hướng dẫn kỹ thuật lấy mẫu. [24] Phạm Hoàng Hộ, Cây cỏ Việt Nam, tập 1, Nxb Trẻ, TP. Hồ Chí Minh, 1999. [25] Phạm Hoàng Hộ, Cây cỏ Việt Nam, tập 2, Nxb Trẻ, TP. Hồ Chí Minh, 2003. [26] Phạm Hoàng Hộ, Cây cỏ Việt Nam, tập 3, Nxb Trẻ, TP. Hồ Chí Minh, 2000. [27] http://www.efloras.org/flora_page.aspx?flora_id=2 [28] http://www.theplantlist.org/ [29] http://www.iucnredlist.org/ [30] Bộ Khoa học và Công nghệ, Viện Khoa học và Công nghệ Việt Nam, Sách Đỏ Việt Nam. Phần II: Thực vật, Nxb. Khoa học Tự nhiên và Công nghệ, Hà Nội, 2007, 612 tr. [31] Nguyễn Khánh Vân, Nguyễn Thị Hiền, Phan Kế Lộc và Nguyễn Tiến Hiệp, Các biểu đồ sinh khí hậu Việt Nam, Nxb. Đại học Quốc gia Hà Nội, 2000, tr. 45, 48, 120, 121. [32] Averyanov L. V., Lộc P. K., Hiệp N. T. & Harder D. K., Phytogeographic Review of Vietnam and Adjacent Areas of Eastern Indochina, Komarovia, 3, 2003, pp. 1-83. [33] Tsujino R. & Yumoto T., Topography-speciﬁc seed dispersal by Japanese macaques in a lowland forest on Yakushima Island, Japan, Journal of Animal Ecology, 78, 2009, pp. 119-125. [34] Đỗ Đình Sâm, Ngô Đình Quế, Nguyễn Tử Siêm và Nguyễn Ngọc Bình, Cẩm nang ngành Lâm nghiệp, Chương Đất và Dinh dưỡng đất, Bộ NN&PTNT, Chương trình hỗ trợ ngành Lâm nghiệp và đối tác, 2006, 143 tr. [35] Li Z. L., Zhang S. L. & Chen D. M., Red bayberry (Myrica rubra Sieb. & Zucc.): A valuable evergreen tree fruit for tropical and subtropical areas, Acta Horticulture 321, 1992, pp.112-121. [36] Sasakawa H., 1995: Effect of Frankia Inoculation on Growth and Nitrogen-Fixing Activity of Myrica rubra Seedlings Prepared Aseptically, Soil Science and Plant Nutrition 41(4): 691-698. [37] Tian X. R., Shu L. F. & He Q. T., Selection of fire-resistant Tree Species for Southwestern China, Forestry Studies in China, 3(2), 2001, pp. 32-38. [38] Deng C. N., Pan X. M., Zhang H. Y. & Pan X. L., Fire-resistance of six tree species to fire probed by chlorophyll fluorescence, Journal of Food, Agriculture & Environment, 10(2), 2012, pp. 1329-1333. [39] Nguyễn Tiến Bân (Chủ biên), Danh lục các loài Thực vật Việt Nam, tập 2, Nxb. Nông nghiệp, 2003, 1203 tr. [40] Nguyễn Tiến Bân (Chủ biên), Danh lục các loài Thực vật Việt Nam, tập 3, Nxb. Nông nghiệp, 2005, 1248 tr.